INNOVATIVE APPROACHES IN FORMING STUDENTS' LINGUISTICAL COMPETENCE - Ochilova Fayyoza Mansurovna (Bright Mind Publishing, 2025)
This article analyzes the process of developing students' linguo-aesthetic competence. The study examines the role of linguo-aesthetic competence in the education system and the importance of both traditional and innovative approaches in its development. The analysis results show that the use of interactive methods, audiovisual technologies, and a multimodal approach effectively contribute to the development of linguo-aesthetic competence. The article provides conclusions on improving the process of forming this competence.
Keywords: Linguo-aesthetic competence, innovative pedagogy, interactive learning, multimodal approach, aesthetic thinking.